Efektivitas Pemberian Olive Oil dan Virgin Coconut Oil (VCO) Topikal untuk Mencegah Striae Gravidarum pada Kehamilan Trimester II - Astri Yulia Sari Lubis; Syarief Thaufik; Melyana Nurul Widyawati; Suhartono Suhartono (Jurnal Riset Kesehatan, 2015)
The objective of study to analyze the differences in the effectiveness of Olive Oil, VCO, and topical placebo to degree of Striae Gravidarum. The research was clinical trials (randomized controlled trial) with a parallel design study for 8 weeks . The samples totaled 54 respondents were randomized with a random permutted blocks technique to allocate the same amount of groups A, B, and C. Analysis of the data to examine differences in the degree of SG group olive oil, VCO, and placebo used Kruskal-Wallis test, significancy p less than 0,05 with 95% confidence intervals. There were significant differences in the degree of striae gravidarum pengolesannya between the two groups using olive oil, VCO, and topical placebo (p = 0.025), are the Olive Oil and VCO (p = 0.031), the VCO and placebo group (p = 0.005). There was differences effects of topical olive oil, VCO, and placebo to SG. The suggestions proposed is the VCO can be used as an alternative in preventing of Striae Gravidarum.